THE IMPACT OF AUDIO-VISUAL MEDIA (YOUTUBE AND TIKTOK) ON THE LANGUAGE DEVELOPMENT OF 5-6 YEAR-OLD CHILDREN(CASE STUDY IN RT.07 DASAN AGUNG PELITA) - Muhammad Abid Al Faqh (Sinar Lima, 2025)
This research is motivated by the phenomenon of YouTube and TikTok as audio-visual-based applications widely used as a means to optimize child development, particularly in the aspect of language development. The purpose of this study was to find out the impact of audio-visual media (Youtube and Tiktok) on the language development of 5-6 year old children in RT.07 Dasan agung Pelita. The method used in this study is a qualitative method, which aims to describe the situation objectively through words and sentences. The results show that YouTube and TikTok have a significant impact on the language development of 5-6 year-old children in RT.07 Dasan Agung Pelita. The identified positive impact is an increase in children's vocabulary through the content they watch. However, there are also negative impacts, such as the potential for addiction in children and a lack of direct interaction with others around them.